(In)compatibility of Evidence Admissibility Limitations with the Fair Resolution of a Civil Dispute - Maculevičienė, Indrė (Teisė, 2026)
he article examines the (in)compatibility of evidentiary admissibility limitations with the fair resolution of civil disputes. Statutory restrictions and prohibitions on the admissibility of evidence serve two functions: firstly, they protect the parties from the use of unlawful or improperly obtained evidence; secondly, they prevent the court from relying on information which, despite being potentially helpful in establishing the factual truth, has been obtained in violation of fundamental legal principles or values protected by law. In this way, balance is maintained between the pursuit of truth and a lawful, fair process, thus safeguarding both individual and public interests. Therefore, limitations on the admissibility of evidence in civil proceedings should be understood as an essential safeguard to ensure that judicial decisions are based solely on lawful, reliable, and properly obtained data.
Keywords: evidence; admissibility of evidence; restrictions on admissibility; secret information